The identity construct of Karim Amir in relation to family, lower middle class struggle, race, sexuality and violence - Dalila Diyana Abd Majid (2011)
This essay aims to explore the identity issues central to Hanif Kureishi's The Buddha of Suburbia. Karim Amir, the protagonist, struggles with his identity formation, essentially having no sense of what it means to be Karim Amir or an Englishman or any individual of his choice because of the circumstances surrounding his existence, including his family, his struggle coming to terms with being part of the lower middle class, the dual heritage of being both Indian and English or neither at all, his sexual orientation and the racial violence which plagues his childhood . This phenomena is made strikingly obvious through the dynamics found within his relationships with characters in the novel, especially his parents because as Karim’s first nurturing caregivers, they impress on him fundamental ideas of identity creation and conception like who is your own person, what does it mean to be your own person, how should this person of your own behave and interrelate with other individuals. My exploration does not aim to resolve this predicament but show how Karim Amir’s state of confusion can be attributed to the incapacity to fully comprehend his individuality, how this relates to his position in society and seamlessly conduct himself appropriately.As Karim moves around socially and geographically, it provides valuable insight into a young man’s journey to find himself, a conquest familiar to anyone who has found themselves thrown into the deep end of the pool without warning when puberty and the disintegration of the nuclear family unit strikes.